Step-by-step explanation:
Next term is - 51
Use formula Tn=a+(n-1)d
a=the first term of the sequence which is - 15
d=the difference between the terms which is - 9
Substitute
Tn=-15+(n-1)(-9)
Tn=-15+9-9n
Tn=-9n-6
From this you will be able to generate all the terms in the pattern
If they say determine the 50th term just substitute 50 by n
Tn=-9(50)-6
Tn=-450-6
Tn=-456
Answer:
each taco is $7.
Step-by-step explanation:
In total he spent $36. He bought a shirt for $22 and a bottle of water for $4.
22+4= 26
36-22= 14
14 divided by 2= 7
Simone would have to bike for at least 34 miles to reach $510
Answer:
(a+5)^2=25 means a^2+5^2=25, a^2=25-25 then a^2=√0, a=0
Answer:
![x=2y+3](https://tex.z-dn.net/?f=x%3D2y%2B3)
Step-by-step explanation:
So we have the equation:
![x-2y=3](https://tex.z-dn.net/?f=x-2y%3D3)
And we want to solve for x. In other words, we want to isolate the x-variable.
So, add 2y to both sides of the equation.
![(x-2y)+2y=(3)+2y](https://tex.z-dn.net/?f=%28x-2y%29%2B2y%3D%283%29%2B2y)
On the left, the 2y cancel. Simplify the right:
![x=2y+3](https://tex.z-dn.net/?f=x%3D2y%2B3)
And we're done!